New insights into cadmium stressful-conditions: Role of ethylene on selenium-mediated antioxidant enzymes - Alves, Leticia Rodrigues [UNESP]; Rodrigues dos Reis, André [UNESP]; Prado, Emilaine Rocha [UNESP]; Lavres, José; Pompeu, Georgia Bertoni; Azevedo, Ricardo Antunes; Gratão, Priscila Lupino [UNESP] (Elsevier, 2019)
Cadmium (Cd) contamination has generated an environmental problem worldwide, leading to harmful effects on human health and damages to plant metabolism. Selenium (Se) is non essential for plants, however it can improve plant growth and reduce the adverse effects of abiotic stress. In addition, ethylene may interplay the positive effects of Se in plants. In order to investigate the role of ethylene in Se-modulation of antioxidant defence system in response to Cd-stress, we tested the hormonal mutant Epinastic (epi) with a subset of constitutive activation of the ethylene response and Micro-Tom (MT) plants. For this purpose, Se mineral uptake, Cd and Se concentrations, pigments, malondialdeyde (MDA) and hydrogen peroxide (H2O2) contents, ethylene production, glutathione (GSH) compound, and superoxide dismutase (SOD), ascorbate peroxidase (APX), catalase (CAT), glutathione reductase (GR) and glutathione peroxidase (GSH-Px) activities were analysed in MT and epi plants submitted to 0.5 mM CdCl2 and 1 μM of selenate or selenite. MT plants treated with both Se forms increased growth in the presence or not of 0.5 mM CdCl2, but not change epi growth. Both Se forms reduced Cd uptake in MT plants and cause reverse effect in epi plants. P, Mg, S, K and Zn uptake increased in epi plants with Se application, irrespective to Cd exposure. Chlorophylls and carotenoids contents decreased in both genotypes under Cd exposure, in contrast to what was observed in epi leaves in the presence of Se. When antioxidant enzymes activities were concerned, Se application increased Mn-SOD, Fe-SOD and APX activities. In the presence of Cd, MT and epi plants exhibited decreased SOD activity and increased CAT, APX and GR activities. MT and epi plants with Se supply exhibited increased APX and GR activities in the presence of Cd. Overall, these results suggest that ethylene may be involved in Se induced-defence responses, that triggers a positive response of the antioxidant system and improve growth under Cd stress. These results showed integrative roles of ethylene and Se in regulating the cell responses to stressful-conditions and, the cross-tolerance to stress could be used to manipulate ethylene regulated gene expression to induce heavy metal tolerance.
Keywords: Antioxidant system; Ethylene; Mutants; Reactive oxygen species; Tomato